Discriminación racial en Alemania: los medios empleados para luchar contra el racismo de los grupos minoritarios y la práctica del racial profiling = Abweichender Titel: Racial Discrimination in Germany : The Means Used to Combat Racism of Minority Groups and the Practice of Racial profiling - Sánchez-Cabezudo Rina, Tiffany-Milagros (Cauriensia, 2025)
In recent years, strong discriminatory behaviors have been originating in European countries that have caused international organizations to further strengthen mechanisms to combat discrimination in general, and racial discrimination in particular. In this article, we will focus on analyzing the situation of minority groups in one of the countries that has suffered most from social exclusion, especially during the dictatorial period of Adolf Hitler, with the persecution of Jews, and which triggered World War II; such is the case of Germany. In addition, we will focus on the study of a practice called racial profiling, which is carried out by the German federal police and which has attracted the attention of international organizations. This practice has been the subject of controversy since it can be considered that the forces of law and order are carrying out their work by paying special attention to groups that are more likely to commit criminal acts.